A study Of semantic and pragmatic features Of concessive conjuncts “still”, “yet” And their equivalents in vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Conducted in a contrastive manner, this thesis discusses the semantic and pragmatic features of concessive conjuncts “still”, “yet” in English and their two most popular equivalents in Vietnamese, i.e. “vẫn” and “chưa”. In order to do this, the theoretical as well as practical matters are taken into consideration. For the theoretical background, we present the definition and classification of conjuncts, conjunctions, prepositions as well as pragmatics and the speech act theory. Meanwhile, in practice, hundreds of sentences including these words are gathered to find out and demonstrate the characteristics in terms of semantic and pragmatic aspects. They are similar and different in many ways; they can reveal the concession, emphasize the comparison or as for the pragmatics, they may illustrate the presupposition, running down or irony, etc. The study aims at helping users of the two languages recognize explicit and implicit meanings of these concessive conjuncts in English and their equivalents in Vietnamese and well apply in communication, teaching and translation.